ANALISIS LITERATUR PENGGUNAAN ICE BREAKING INTERAKTIF SEBAGAI STRATEGI PENGELOLAAN KELAS DI SEKOLAH DASAR - Purba, Helena Auria Br; Putri, Icha Aprilia Meliani; Syaqib, Khaila Azzahra; Ma'arip, M. Ridho Risdian; Huda, Lutifa Nurul; Iskandar, Sofyan (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine the role of interactive ice breaking as a classroom management strategy in elementary schools, focusing on its contribution to improving students’ concentration, motivation, participation, and creating a supportive learning environment. The study employed a Systematic Literature Review (SLR) by analyzing 15 scientific articles on the use of ice breaking in elementary education. The data were secondary sources collected through systematic literature searching and recorded using a literature review checklist. Data analysis involved reduction, presentation, and synthesis of findings. The results revealed three main patterns. First, interactive ice breaking is effective in increasing students’ focus, motivation, and engagement, reducing boredom, and improving readiness to learn, with some studies reporting focus improvements of up to 85%. Second, it functions as a classroom management strategy that helps create a conducive and collaborative atmosphere, assists teachers in stabilizing classroom conditions, reduces uncooperative behavior, and enhances student interaction. Third, the literature highlights its innovation and integration with the Merdeka Curriculum and technology, such as visual media and digital applications, which help reduce distractions and suit digital-era learners. Overall, this review confirms interactive ice breaking as an important pedagogical strategy for effective classroom management and for promoting active, enjoyable, and student-centered learning.